(untitled) (Nexus International Journal of Science and Education, 2024)
The study assessed the relationship between MTB-MLE implementation and Kindergarten infrastructure in Banaybanay District, Davao Oriental. This study used a non-experimental descriptive-correlational research design, where it utilized an adapted survey instrument to gather responses from the randomly selected 120 teacher respondents. Data gathered were treated using Mean scores with descriptive interpretation, Pearson r and Simple Linear Regression Analysis. Findings revealed that the extent of MTB-MLE implementation shows that availability of learning materials, teacher training, policy compliance, and language of instruction are moderately extensive, while the extent of kindergarten infrastructure shows that inclusivity, cultural relevance, and classroom availability are extensive, while facilities and amenities are moderately extensive. There is a significant relationship between MTB-MLE Implementation and Kindergarten Infrastructure and resource allocation. All domains of MTB-MLE implementation in terms of language of instruction, teacher training, availability of learning materials and policy compliance significantly influenced the kindergarten infrastructure and resource allocation. Future research may create a collaborative culture among teachers to share insights, resources, and effective instructional strategies.